Creating the regulatory framework for Fintech in Costa Rica (National Administration Journal, 2023)
This article will describe the elements of the FinTech roadmap that the Superintendencies, the National Council for Supervision of the Financial System (CONASSIF), and the Central Bank of Costa Rica (BCCR), have been implementing for the design of a regulatory framework for FinTech in the country. Special attention will be given to the recently created “Centro de Innovación Financiera (CIF)” and the description of a possible vision for the future.The views and opinions expressed here are those of the author and do not necessarily reflect the official position of any of her associated institutions.
Keywords: Framework; Fintech; regulatory